Total Protein Requirements of Beef Cattle III: Match the Diet to the Cattle Requirements - Matt Hersom; Jeffrey N. Carter (EDIS)
Revised! AN188, a 3-page fact sheet by Matt Hersom and Jeffrey N. Carter, provides realistic examples from different productive states to demonstrate the function of rumen microorganisms and the differences in the nutrient profile of feedstuffs. Includes references. Published by the UF Department of Animal Sciences, April 2010.